Climate-smart agriculture and development practices in Egypt: Report on a policy seminar event - Hassan, Ganna; Tarek, Abdallah (International Food Policy Research Institute, 2025)
This policy note summarizes presentations and discussion shared during the workshop held in Cairo on May 25th 2025, as part of the Bridging Evidence and Policy (BEP) seminar series, a collaborative initiative by the Egyptian Food Bank (EFB), the International Food Policy Research Institute (IFPRI), and the Sawiris Foundation for Social Development (SFSD) which brings together researchers, policymakers, and development practitioners.